2015
DOI: 10.1016/j.jconrel.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial modification of urinary catheters with antimicrobials to give long-term broadspectrum antibiofilm activity

Abstract: Catheter-associated urinary tract infection (CAUTI) is the commonest hospital-acquired infection, accounting for over 100,000 hospital admissions within the USA annually. Biomaterials and processes intended to reduce the risk of bacterial colonization of the catheters for long-term users have not been successful, mainly because of the need for long duration of activity in flow conditions. Here we report the results of impregnation of urinary catheters with a combination of rifampicin, sparfloxacin and triclosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 31 publications
1
107
0
Order By: Relevance
“…Catheterisation is one of the most common modern medical procedures, where the insertion of a urinary catheter bypasses the normal host defences facilitating the entry of pathogens into the bladder [2]. The bacterial pathogens most commonly associated with catheter-associated urinary tract infections (CAUTIs) are Escherichia coli and Proteus mirabilis [4]. An infection associated with Proteus mirabilis frequently leads to blockage of catheters because of biomineralisation and formation of a crystalline biofilm through the bioconversion of urinary ammonium and other salts, causing obstruction of catheter lumen and kidney infection and septicaemia [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Catheterisation is one of the most common modern medical procedures, where the insertion of a urinary catheter bypasses the normal host defences facilitating the entry of pathogens into the bladder [2]. The bacterial pathogens most commonly associated with catheter-associated urinary tract infections (CAUTIs) are Escherichia coli and Proteus mirabilis [4]. An infection associated with Proteus mirabilis frequently leads to blockage of catheters because of biomineralisation and formation of a crystalline biofilm through the bioconversion of urinary ammonium and other salts, causing obstruction of catheter lumen and kidney infection and septicaemia [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial pathogens most commonly associated with catheter-associated urinary tract infections (CAUTIs) are Escherichia coli and Proteus mirabilis [4]. An infection associated with Proteus mirabilis frequently leads to blockage of catheters because of biomineralisation and formation of a crystalline biofilm through the bioconversion of urinary ammonium and other salts, causing obstruction of catheter lumen and kidney infection and septicaemia [4][5][6]. Klebsiella pneumoniae is a gastro-intestinal bacterium and an opportunistic pathogen associated with septicaemia, pneumonia, urinary tract infections, and meningitis, and can persist within the urinary tract despite appropriate antibiotic treatments [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of these infections becomes difficult, especially when an opportunistic and drug-resistant pathogen like Pseudomonas aeruginosa is the etiological agent. P. aeruginosa and Candida species are pathogens frequently isolated from long-term-catheterized patients subjected to repeated dosage of antibiotics (6). In a recent study conducted in India, CAUTIs were reported to be the second most frequently detected infection in health care settings and P. aeruginosa as the single most causative organism of HAI (7).…”
mentioning
confidence: 99%